2011
DOI: 10.1371/journal.pone.0027133
|View full text |Cite
|
Sign up to set email alerts
|

Benznidazole Therapy Modulates Interferon-γ and M2 Muscarinic Receptor Autoantibody Responses in Trypanosoma cruzi-Infected Children

Abstract: ObjectiveThe presence of autoantibodies with adrenergic and cholinergic activity, capable of triggering neurotransmitter receptor-mediated effects, has been associated with pathogenesis in T. cruzi-infected hosts. The goal of this study was to investigate the production of anti-M2 muscarinic receptor autoantibodies (Anti-M2R AAbs) as well as the IFN-γ profile in children at the early stage of Chagas disease, and to examine whether trypanocidal chemotherapy with benznidazole (BZ) could modify both response patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
(41 reference statements)
2
11
0
Order By: Relevance
“…The reduction in CAM expression and, consequently, cell adhesion was independent of the trypanocidal activity of benznidazole. Indeed, the anti-inflammatory effect of benznidazole had already been reported [ 33 ]. In experimental sepsis models, benznidazole attenuated NF-κB and the MAPK pathway activities, highlighting its immunomodulatory capacity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in CAM expression and, consequently, cell adhesion was independent of the trypanocidal activity of benznidazole. Indeed, the anti-inflammatory effect of benznidazole had already been reported [ 33 ]. In experimental sepsis models, benznidazole attenuated NF-κB and the MAPK pathway activities, highlighting its immunomodulatory capacity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…35 Its immunomodulatory effect goes further through the observation that the benznidazole is able to inhibit inflammatory cytokines, autoantibodies, nitric oxide production, and also leukocyte recruitment into the heart during T. cruzi infection in human and experimental models. [36][37][38][39] In these studies, the toxicity of the benznidazole overrides the cardiac beneficial effects since activation and/or misbalanced of the host inflammatory response become detrimental to the heart function. Yet far from a cure for chronic stage of the infection, a novel therapeutic strategy has been proposed in which immunomodulation in the absence of immunosuppression could be beneficial to the host during chronic T. cruzi infection.…”
Section: Discussionmentioning
confidence: 99%
“…Since increased fibrosis is a trigger for the development of arrhythmias, our findings are consistent with the effects of Bz treatment in collagen deposition previously reported. Recently, Cutrullis et al [10] reported a significant reduction of serum anti-M 2 -CR titers in children in the indeterminate form of Chagas disease when submitted to Bz treatment, however they could not associate this finding with heart dysfunction as the patients did not show any ECG or ECHO alterations.…”
mentioning
confidence: 96%